Application of base station with array of intelligent antennas in the energy distribution sector - KLEINAU, Bruno Agra (2022)
The use of Distribution Automation Systems has grown significantly in electricity companies in recent years. The main reason for this is the need to have a smarter network, in order to reduce the time of power interruption. For such applications, communication using Radio Frequency is preferred because this solution is more reliable than 3G/4G and cheaper than fiber optics. In this context, it is of utmost importance to have a more efficient Base Transceiver Station (BTS) that can cover the communication of a larger area. In this work, the mathematical concepts of an intelligent antenna array, as well as the logical operation of an intelligent radiation system controller are presented. Such a system receives as inputs the geographic coordinates of network elements and automatically feeds an intelligent Yagi-Uda antenna array with the appropriate parameters, in order to optimize the radiation pattern in the desired directions. The newly presented model uses a stochastic optimization method to automatically achieve a set of optimal electrical parameters to excite the array, and efficiently direct its beams in a fully controlled way. Thus, the results obtained indicate that the proposed intelligent scheme allows the energy optimization of the antenna system, reducing by 61% the number of BTS needed to cover the same area, when compared to traditional collinear antenna systems.